EFFECT OF SOCIAL DOMINANCE ORIENTATION AND RIGHT-WING AUTHORITARIANISM ON RELATIONSHIP BETWEEN PERSON-JOB FIT AND ORGANIZATION CITIZENSHIP BEHAVIOR: AN ANALYSIS THROUGH HIERARCHICAL LINEAR MODELLING - Dr. Pardeep Bawa Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper intends to examine the effect of social dominance orientation (SDO) and rightwing authoritarianism (RWA) on relationship between person-job fit (PJF) and organization citizenship behavior (OCB). Data were collected from 236 principals of K12 private schools in Chandigarh tri-city (Chandigarh, Mohali and Panchkula) in India. Data was analyzed using Structured Equation Modelling (SEM). Results were cross validated with the help of hierarchical liner modelling. Results showed that not only SDO and RWA affect PJF but moderates the link between PJF and OCB.